Evaluating clerkship competency without exams. (2nd December 2019) - Cianciolo, Anna T; Hingle, Susan; Hudali, Tamer; Beason, Austin M
Summary: Background: Using examination scores for grading clerkship threatens students' engagement at a time when clinical immersion is critical for socialising into medicine. Narratives of student performance, composed during training by multiple preceptors across diverse settings, may be used to judge competence instead. Preceptor commentary is not trusted as a basis for grading, but the alignment between performance narratives and examination scores has not yet been investigated. Methods: Performance data were gathered retrospectively from five cohorts of internal medicine clerkship students at one institution. The correlation between end‐of‐rotation examination scores and the grading committee's ratings of student competency based on preceptors' comments was examined. Patterns in the performance narratives of high‐ and low‐scoring students were also explored. Results: The grading committee's narrative‐based ratings of student competence were correlated with examination scores. The majority of preceptors' comments were positive and professionalism‐oriented, although students who scored lowest on exams received fewer comments overall and more recommendations for improvement than their highest‐scoring peers. Recommendations for the lowest‐scoring students equally emphasised knowledge, clinical skill and professionalism, whereas recommendations to highest‐scoring students emphasised knowledge and clinical skill at more than twice the rate of professionalism. Discussion: Clerkship preceptors' narratives of student performance can inform competency judgements that are grounded in actual workplace learning and are related to the independent examination of knowledge and clinical performance. Using performance narratives as the basis for grading may be a viable approach to balancing learning and assessment needs during core clerkship block rotations.